Los costes de la Investigación y la Docencia cuando se utilizan animales de laboratorio. Resumen - Gil Castillo, Juan Félix; Gaínza Leyva, Juana Claribel; Alerm González, Alina; Barrios Rosquett, Lázara Silvia (Revista Habanera de Ciencias Médicas, 2005)
Los centros de Educación Médica Superior no se autofinancian, sino que tienen un presupuesto asignado para sus funciones. Entre esas funciones, las docentes y las de investigación que utilizan animales de laboratorio son numerosas y se realizan durante todo el curso escolar. Precisamente por ser presupuestadas, los profesores e investigadores de estos centros no se percatan de cómo incrementan los costes de cada actividad en el uso de los animales de experimentación. Esos costes se multiplican cuando los animales solicitados no se utilizan y envejecen en el Bioterio. OBJETIVOS 1. Estimar los costes aproximados de los animales solicitados por algunos departamentos del ICBP “Victoria de Girón”. 2. Evaluar prospectivamente los posibles costes de las actividades de docencia e investigación. 3. Evidenciar el manejo inadecuado que se realiza en relación con la decisión de solicitar animales para la docencia y la investigación. MATERIALES Y METODOS El cálculo se realizó a partir de los pesos de animales más solicitados, considerando 100 animales y una estadía de 180 días en el Bioterio. Los costes para los animales se estimaron de acuerdo con el promedio entre ambos sexos, pero no cuestan igual. Los costes por concepto de consumo, agua y electricidad son estimados. Hasta ahora no se lleva control de ese aspecto. Se incluyen los salarios de un técnico, un cuidador y un técnico de laboratorio y costes por concepto de transportación y embalaje, pues el centro suministrador los contempla en las facturas que emite. No se considera el pago a los investigadores que participan en el trabajo con los animales. RESULTADOS Los costes de las investigaciones por concepto solamente del empleo de animales de laboratorio oscilaron entre 8 659.00 y 105 520.00.A esto se le añade que los animales no siempre se utilizan y, por tanto, permanecen mucho tiempo en el Bioterio, y esto incrementa los costes. CONCLUSIONES Los costes por concepto de animales de experimentación se encarecen en la medida que los profesores e investigadores hacen las solicitudes sin conocimiento del componente económico de esta actividad. Es necesario divulgar entre los profesionales que trabajan en los CEMS, las normas éticas y económicas que rigen el empleo de animales de experimentación para que utilicen sólo los imprescindibles y en el tiempo en que fueron planificados ABSTRACT: The costs of investigations and teachings using lab animals. INTRODUCTION Superior Medical Education Centers are not self financed but have a budget assigned to their functions. Among these functions, teaching and investigative human resources who utilize lab animals are many, and those functions are performed during the whole school year. Precisely because they have a budget, professors and investigators in each center don’t realize how the use of these lab animals increases the costs of each activity. These costs are multiplied when these animals are not utilized and get old at the Bioregion. OBJECTIVES 1.To guesstimate the approximate costs of the requested animals by some departments at the Preclinical Basic Sciences Institute (PBSI) “Victoria de Girón”. 2. To prospectively evaluate the costs of the teaching and investigation activities. 3. To point out the inadequate management concerning the decisions of requesting lab animals for teaching and investigation. MATERIAL AND METHODS The reckoning was done on the basis of the most solicited animals, considering 100 animals and a stay of 180 days in the Bioregion. The costs for animals were anticipated considering an average between both sexes, though they don’t cost the same. The costs considering consumption of water and electricity were estimated because to the present day, there is no calculation made in that point of view for the moment. There are included the salaries of a technician, an animals carer and a lab technician, plus costs by concept of transportation and wrap up though the suministrator center emit the costs slips.The payment to investigators who participated in the investigation with animals was not considered. RESULTS The costs of investigations taking in consideration only the animals expenses fluctuate between 8659.00 and 105520.00. To this, we have to add that these animals are not always utilized therefore, they remain a long time in the Bioregion, and therefore the expenses are increased. CONCLUSIONS The costs by concept of experimentation animals are increased in the same way professors and investigators request animals without knowledge of the economic complement of this activity. It is necessary to make known, among the workers of these centers, the ethical and economical rules and regulations inn the employment of experimentation animals for them to be utilized only in very particular activities and during the time that they were planned.